Free-range rearing density for male and female Milanino chickens: carcass yield and qualitative meat traits - Silvia Cerolini (Journal of Applied Poultry Research, 2019)
SUMMARY: The Milanino is a heavy Italian chicken breed and represents an important genetic resource for alternative production systems. In order to support its promotion in the market according to consumer expectations on healthy nutrition and animal welfare, this trial aims to study the slaughter performance and the meat quality in male and female Milanino chickens kept at different rearing density in a separate-sex free-range system. A total of 140 birds (70M:70F) were reared in outdoor pens from 75 to 235 d of life according to the following experimental groups (35 birds/group): M2) males in 2 m2/bird; F2) females in 2 m2/bird; M10) males in 10 m2/bird; F10) females in 10 m2/bird. At 235 d of age, 6 birds per group were slaughtered. Slaughter performance and meat quality were assessed. The Milanino chicken is characterized by high carcass weight and carcass yield among local chicken breeds, and a rearing density of 10 m2/bird is recommended for male birds to obtain heavier carcasses. Milanino meat appears bright and intensely colored, and it is characterized by high protein and low fat contents compared with the standard broiler meat. Total lipids of Milanino meat are characterized by a healthy fatty acid composition, corresponding to a high PUFA/SFA ratio. Milanino breast meat is a good supply of nutraceutical PUFA with a positive low n-6/n-3 PUFA ratio. The ability of the Milanino breed either to synthesize or to transfer to tissue a high quantity of PUFA relevant for human health could be a key factor for its economic valorization.